A neologia em sala de aula: análise de atividades da coleção didática Português - uma proposta para o letramento - Priscila de Resende (2014)
In general, the language tends to change every day, following the cultural evolution of language community. Because it, inevitably, certain words are no longer used by other speakers and appear others, according to need. The creation of new words and reuse of existing words from new meanings, then, constitute a general process of development of the lexicon of a language. This research, essentially qualitative, aims to analyze and describe how these new words, lexical neologisms are taught in schools through the portuguesa textbook. From what can be observed today in several studies, concerning to the teaching of vocabulary, the lexical neology remains, with rare exceptions, marginalized in the classroom and / or in the textbooks of the portuguese language. Thus, our analysis focused on the didactic collection "Português: uma proposta para o letramento", the author Magda Soares. This choice was the fact that in this collection there is an "innovative" proposal related to the teaching of the lexicon, in particular to the creation of new words (lexical neologisms) since these are studied from the study text directed, within a context, leading the student to also infer knowledge. The concept of lexical neologism adopted here follows the lexicographical criteria, based on a corpus of exclusion, formed by the main brazilian portuguesa dictionaries, with their newest editions: Dicionário Aurélio da Língua Portuguesa (2010), 5ª ed., (versão eletrônica), Dicionário Eletrônico Houaiss da Língua Portuguesa (2009) e o Dicionário Caldas Aulete (2013), versão on-line. In order to contribute suggestions for teaching neology, we present a sample of activities for teaching neology the perspective of the development of lexical competence.